Responsiveness of motion sensors to detect change in sedentary and physical activity behaviour - Swartz, Ann M (Br J Sports Med, 2014)
BACKGROUND: The purpose of this study was to determine the responsiveness of two motion sensors to detect change in sedentary behaviour (SB) and physical activity (PA) during an occupational intervention to reduce sitting time. METHODS: SB and PA were assessed using a hip-worn Actigraph GTX3 (AG) and a thigh-worn activPAL (AP) during three consecutive workdays throughout baseline and intervention periods. Mean scores at baseline and intervention were estimated by hierarchical linear models (HLM) with robust SEs, adjusting for random variance of average scores between participants. Change scores (mean baseline minus mean intervention) were calculated for each device. Response to change was assessed for each device using the standardised response mean. RESULTS: 67 adults (45±11 years; 29.3±7.7 kg/m(2)) wore the acceleration-based motion sensors for 8.3 (SD=1.2) and 8.3 (SD=1.1) h during the baseline and intervention periods, respectively. HLM showed that AP sitting/lying time (−16.5 min, −5%), AP stepping (+7.5 min, 19%), AP steps/day (+838 steps/day, +22%), AP sit-to-stand transitions (+3, +10%), AG SB (−14.6 min, −4%), AG lifestyle moderate-intensity PA (LMPA, +4 min, +15%) and AG MPA (+3 min, 23%) changed significantly between the baseline and the intervention period. Standardised response means for AP sitting/lying time, stepping, steps/day, sit-to-stand transitions and AG SB, LMPA and MPA were above 0.3, indicating a small but similar responsiveness to change. CONCLUSIONS: Responsiveness to change in SB and PA was similar and comparable for the AP and AG, indicating agreement across both measurement devices.